Instrument of student assessment based on nursing managerial competences - Tronchin,Daisy Maria Rizatto (2008)
When the students conclude the Curricular Training on Nursing Management discipline from the Professional Guidance Department at USP School of Nursing (EE-USP), they answer a self-assessment which scores from zero to ten the trainee program and a also participates in a group assessment, carried out by the professor and nurses from the units, practice fields. In this process, it was applied an instrument aiming at measuring students performance concerning managerial contents. With the purpose of accompanying students' background development according to the Pedagogical-Political Project by EE-USP, aiming at a meaningful learning that minimizes the theory/practice dichotomy, a new instrument was developed to assess students having nursing managerial competences as baseline. This study aims at describing the experience of building up an instrument for students assessment related to the nursing managerial competences. This paper has the purpose of reporting the following prognosticators: planning, decision-taking, supervision, human resource management, material resource management, information system, interpersonal relationship, responsibility, commitment and case study.